Transforming Lives: Oloruntobi Stephen's Journey with Farmers Outreach - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2025)
In this video, Oloruntoba Olufemi, Chairman of the Cassava Growers Association in Ondo State, found himself in an unexpected role of a consultant after attending Radio IITA's training.